LITERASI DEMOKRASI DAMAI DI ERA DIGITAL PADA PERWAKILAN PELAJAR SMPN 4 SURAKARTA - Haqqu, Rizca; Mahadian, Adi Bayu; Satria Putri, Berlian Primadani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Based on the information from the Principal of SMPN 4 Surakarta, many of her students experienced bullying when using social media and inappropriately expressed their freedom of opinions. As a result, a team of lecturers from the Faculty of Communication and Business, Telkom University conducts a Community Service Activity at SMPN 4 Surakarta entitled "LITERATION OF PEACE DEMOCRACY IN THE DIGITAL ERA IN STUDENT REPRESENTATIVES OF SMPN 4 SURAKARTA" with the aim of helping schools and their students maximize the use of gadgets effectively and safely. This topic is interesting and important to discuss because currently the school is one of the schools that is experiencing climate change in the learning process and social interaction between students due to the zoning system. The aim of this Activity is so students become people with good character and become responsible when using their social media. With the use of participatory, educative method and training the result shows that SMPN 4 Surakarta students, have successfully carried out all the trainings in two different sessions. The first one focuses on Communication area while the second one focuses on the Democracy Literacy. Even though they were forced to get out of their comfort zone in expressing their opinions, SMPN 4 Surakarta students were finally able to apply what they have learned from this training, as evidenced by the presentation at the end of the activity. Keywords: Social media, Literasi Demokrasi, Digital Era